Automatic identification technologies within distribution logistics from the perspective of efficiency of the identification process - Chocholáč, Jan; Hruška, Roman; Kučera, Tomáš; Machalík, Stanislav; Hyršlová, Jaroslava (Melandrium, 2019)
This article deals with the use of automatic identification technologies within distribution logistics. Effective set up distribution logistics makes a significant contribution to improving the customer service of companies. Nowadays, when the importance of e-commerce is growing, it is necessary to efficiently set up logistics processes and use appropriate technologies. The “last mile” distribution is essential from the perspective of distribution logistics. It is the last stage in the distribution of consignments to the final customer from the distribution centres. In terms of automatic identification technologies barcodes are mainly used currently, but also quick response codes are increasingly popular. However, there are other automatic identification technologies, such as radio frequency identification technology. Radio frequency identification technology enables to get real, accurate, and timely data that is needed for effective distribution. The aim of this article is to compare selected parameters of the efficiency of the automatic identification process of consignments within distribution logistics. Experimental testing of selected automatic identification technologies was carried out in a specialized laboratory of automatic identification.
Technologie automatické identifikace v rámci distribuční logistiky z hlediska efektivity procesu identifikace
Keywords: automatic identification technologies; distribution logistics; radio frequency identification technology; technologie automatické identifikace; distribuční logistika; technologie radiofrekvenční identifikace